2018
DOI: 10.3892/or.2018.6211
|View full text |Cite
|
Sign up to set email alerts
|

Targeting bladder cancer using activated T�cells armed with bispecific antibodies

Abstract: In the present study, we aimed to investigate whether EGFR or HER2 may serve as a target for T cell-mediated immunotherapy against human bladder cancer. Expression of EGFR and HER2 was detected on the surface of bladder cancer cells, including Pumc-91 and T24 cells, and their chemotherapeutic drug-resistant counterparts. Activated T cells (ATCs) were generated from healthy PBMCs that were stimulated by the combination of anti-CD3 monoclonal antibody and anti‑CD28 monoclonal antibody in the presence of interleu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Higher CD3 infiltration exhibited improved survival of BLCA, while the correlations of CD3E and BLCA have not been investigated. However, targeting immunotherapy for BLCA using anti-CD3×B7-H3, anti-CD3×CD155, and anti-CD3xEGFR or anti-CD3xHER2 bispecific antibody may provide novel strategies for BLCA therapy ( 40 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Higher CD3 infiltration exhibited improved survival of BLCA, while the correlations of CD3E and BLCA have not been investigated. However, targeting immunotherapy for BLCA using anti-CD3×B7-H3, anti-CD3×CD155, and anti-CD3xEGFR or anti-CD3xHER2 bispecific antibody may provide novel strategies for BLCA therapy ( 40 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Various benefits are attributed to this strategy: (1) T cells are already activated when they arrive to the tumour site, thus affording a quicker and more efficient response; (2) T cells (from the patient or healthy donor) are activated and selectively directed to tumour cells; (3) T cells are cultured ex vivo and multiplied before being armed, thus offering an increased pool of available T cells after administration, particularly for patients with low T cell levels; (4) the total amount of BsAb required is lower when used with armed activated T cells (up to 200 times lower) when compared with the BsAb used as a single agent, potentially reducing the adverse events commonly seen with direct BsAb administration; and (5) a better pharmacokinetic profile can be obtained as clearance is reduced when the BsAb is attached to an effector cell and it can also benefit from the natural T cell capacity to extravasate and travel between endothelial barriers to more easily reach the tumour. [158][159][160] Currently, 17 clinical trials are referenced that use BATs (clinicaltrials.gov), among which 13 are using BATs as single agents (4 are used in combination) and 15 of them are evaluated for solid tumour treatment, probably illustrating the better efficacy and tumour penetration of BATs when compared to classical BsAbs (Fig. 3, top and bottom right dials).…”
Section: Immune Cell Engager Familymentioning
confidence: 99%
“…In 2018 Juan Ma and coworkers generated CD3×EGFR and CD3×HER2 bispecific antibodies by reacting the anti-epidermal growth factor receptor (EGFR) mAb Cetuximab or the anti-HER2 mAb Trastuzumab, respectively, with sulfo-succinimidyl 4-(N-maleimidomethyl)cyclohexane-1-carboxylate (sulfo-SMCC), followed by conjugation with OKT3 after activation with Traut’s reagent ( 62 ). The mouse-derived OKT3 mAb recognizes the CD3ϵ domain in the T cell receptor (TCR) complex and is commonly used for the construction of T cell engagers, as e.g., Blinatumomab ( 63 ).…”
Section: Bispecific Antibodiesmentioning
confidence: 99%
“…The mouse-derived OKT3 mAb recognizes the CD3ϵ domain in the T cell receptor (TCR) complex and is commonly used for the construction of T cell engagers, as e.g., Blinatumomab ( 63 ). By analyzing human-derived active T cells, it could be demonstrated that the bispecific constructs exhibited a stronger cytotoxic activity against bladder cancer cells and mediated secretion of the activation markers Interferon gamma (IFN-γ), tumor necrosis factor alpha (TNF-α), and IL-2 ( 62 ). The following year, the same group utilized this system to generate a CD3×CD155 bispecific antibody ( 64 ).…”
Section: Bispecific Antibodiesmentioning
confidence: 99%